Readiness of economics students for industry 4.0: A case study at private Universities in Vietnam - Ngoc, Phi Nguyen Tran; Thuy, Phuong Nguyen Thi; Trong, Nhan Pham Nguyen; Bich, Tuyen Vo; Mai, Lan Nguyen (International research journal of management, IT and social sciences, 2022)
The present study aimed to qualitatively investigate the readiness for The Fourth Industrial Revolution (Industry 4.0) of economics majors at Vietnam’s private universities. Initially, A survey questionnaire was built to collect data from 350 students majoring in economics at private universities in Vietnam. The rate of valid answers is 100% (N=350). Descriptive statistics and regression analysis were used to analyze quantitative data. Through the regression analysis, findings confirmed a research representative model which had previously hypothesized that perceptions, tech skills, and non-tech skills of Vietnamese economics majors are correlated to their readiness for Industry 4.0. The findings of this study suggest that higher education plays a crucial role in heightening undergraduates’ skills to gear up for their future careers during this disruptive development. The analysis results of the article can be used as a reference to increase college students' readiness toward IR 4.0, thereby ensuring the quality of students after graduation to meet the needs of society